Intentionality and Frege’s Puzzle - Mota Pinto, Sílvio (2015)
What are the absolutely essential features of the intentionality of our beliefs and desires? Some philosophers since Franz Brentano have proposed at least two: i) the intentional objects of our mental states may well not exist in reality; ii) these intentional objects are not sufficient to identify our intentional states about them. If we accept these conditions, then a distinction is forced upon us, that is: the distinction between content and object, which is the one Frege proposed when he suggested a puzzle would arise if we did not distinguish the sense of an expression —for example, a singular term— and its reference. In this paper, I will show that Frege’s puzzle points to a philosophical theory of the intentionality of our thought, which is, in some interesting sense, more satisfactory than the one underlying the so-called theories of direct reference like, for instance, Salmon’s as presented in his classical 1983 book. But, contrary to what other adepts of direct reference like Stavroula Glezakos claim, the Fregean theory of intentionality and the sense-reference distinction is quite independent of the puzzle presented at the start of “Über Sinn und Bedeutung”.